Kajian Gender Perspektif Hadis Nabi - Supardin, Supardin (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
Understanding of gender concept is still varied, depending on the approach used and the stand point taken in observing subjects of discussion with regards to gender. Some perceive that gender issue is not a problem, as long as the value and dignity of women is well understood and preserved. In addition, some others consider that the values contained in gender concept are not contradictive to the virtue and principles of Islam, so that a gender perception in Islam is acceptable.  The subject matter examined in this article is concerning the comprehension of gender in the perspectives hadith. The method implemented is criticism of sanad and matan of hadith with historical and contemporary approaches. Upon accomplishment of this study it is found that according to the Prophet’s tradition, men and women are bound within a partnership in all respects, except for certain situations such as natural functions inherent in a person, both men and women.